1950
DOI: 10.1111/j.1744-7348.1950.tb00969.x
|View full text |Cite
|
Sign up to set email alerts
|

The Toxicity of Certain Synthetic Organic Compounds to the Fruit‐tree Red‐spider Mite

Abstract: The acaricidal activity of ninety synthetic organic compounds has been investigated in the laboratory. Considerable differences were found between the winter eggs, the summer eggs and the adult female stages of the fruit‐tree red‐spider mite (Meta‐tetranychus ulmi (Koch)) in their susceptibility to many of the compounds but two substances, namely azoxybenzene and n‐dodecyl thiocyanate, were appreciably toxic to all three stages. Of the compounds showing promise against summer eggs and mites, bis‐(p‐chloropheny… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

1951
1951
2004
2004

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(4 citation statements)
references
References 7 publications
0
4
0
Order By: Relevance
“…Researchers in the mid to late 1900s observed that alkyl thiocyanates could under appropriate enzymatic conditions release HCN, and they went on to explore the agrochemical potential of this effect. For example, C 12 and C 13 n-alkyl and sec-alkyl thiocyanates were noted to be outstanding insecticides against adult female fruit-tree red spider mites, 15 while various other alkyl thiocyanates were described as lethal to mice and houseflies 16 and selected beetles 17 through the action of HCN. Although these early investigations focused on synthetic alkyl thiocyanates, it has long been known that certain plants and insects employ HCN as a defensive agent through the intermediary of cyanogenic glycosides.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…Researchers in the mid to late 1900s observed that alkyl thiocyanates could under appropriate enzymatic conditions release HCN, and they went on to explore the agrochemical potential of this effect. For example, C 12 and C 13 n-alkyl and sec-alkyl thiocyanates were noted to be outstanding insecticides against adult female fruit-tree red spider mites, 15 while various other alkyl thiocyanates were described as lethal to mice and houseflies 16 and selected beetles 17 through the action of HCN. Although these early investigations focused on synthetic alkyl thiocyanates, it has long been known that certain plants and insects employ HCN as a defensive agent through the intermediary of cyanogenic glycosides.…”
Section: Resultsmentioning
confidence: 99%
“…The residue was partitioned between H2O (10 mL) and Et2O (10 mL), and the aqueous phase extracted with Et2O (3 × 10 mL). The combined organic phase was washed with brine (10 mL), dried (anhydrous MgSO (15). A mixture of commercially available 9-bromo-1-nonanol (5 g, 22.4 mmol), dihydropyran (2.1 mL, 23.3 mmol), and concentrated HCl (22 µL) was stirred at RT for 18 h. The reaction mixture was diluted with Et2O (20 mL) and washed with H2O (20 mL), saturated NaHCO3aq (2 × 20 mL), and brine (20 mL), then dried (anhydrous MgSO4), filtered, and concentrated under reduced pressure.…”
Section: Animal Material See Refmentioning
confidence: 99%
“…The value of study of the inter-relation of the host plant and the pest or disease is illustrated by the work of Wormald (1932), the founder of the Plant Pathology Section, on Bacterial Canker, of Keyworth (1942) on the Verticillium W ilt diseases, of Moore (1950) on Brown R ot of apples, plums, etc., and by th a t of Dicker (1951) on fruit aphids, and of Massee and others on the Fruit Tree Red Spider Mite (Blair 1951). Parallel investi gations of control measures, of the mode of action of fungicides and insecticides (Eaton & Davies 1950), and of methods for their detailed study in the field and laboratory (Moore 1947;Steer 1937), have assisted in relating control measures to the biological characteristics of host and pest.…”
Section: Study Of Infection Of the Raspberry Bymentioning
confidence: 99%
“…Eaton and Davies (13) found that diphenyl sulfone was an active acaricide but it was adversely phytotoxic. p-Chlorophenyl phenyl sulfone was also active, but bis(p-chlorophenyl)sulfone was less active.…”
Section: Diphenyl Sulfones Sulfides and Sulfonatesmentioning
confidence: 99%